Noncommunicable Disease Risk Factors in Developing Countries : Policy Perspectives - Kostova, Deliana (Elsevier, 2018)
Following advances in infectious disease control, noncommunicable diseases (NCDs) have overtaken other conditions as causes of premature death and disability in lower-income nations. The largest portion of the NCD burden in low- and middle-income countries (LMICs) is represented by cardiovascular diseases (CVD), followed by cancer, diabetes and chronic respiratory disease (World Health Organization, 2016). Although NCDs are often considered to be diseases of ageing, the NCD crisis in developing countries does not appear to be explained solely by longer life spans; the growth in NCD deaths and disability in these countries has occurred at a faster rate than the contemporaneous decline in communicable diseases (Stuckler, 2008). Specific circumstances that worsen NCD outcomes in LMICs relative to high-income countries are the timing of disease onset and the level of treatment after onset. NCDs in LMICs tend to occur earlier in life (WHO, 2016; (Institute for Health Metrics and Evaluation, 2013)), and may not receive adequate treatment once they occur (Cameron et al., 2011). Health systems in LMICs may not be equipped to address the needs of the chronically ill, and long-term treatment may not be accessible. This adverse combination of factors results in NCD outcomes that have broad societal, economic, and health security consequences in developing countries. Recognizing the role of NCDs as an impediment to international development, the 2030 Agenda for Sustainable Development has identified the reduction in premature NCD mortality among its primary targets (United Nations, 2015).